Heavy metals (Cd, Pb and Ni) in fish species commercially important from Magdalena river, Tolima tract, Colombia - Noreña-Ramirez, Diana Alexandra (Revista Tumbaga, 2012)
Water quality of the Magdalena River, main waterway of Colombia, has been severely damaged by the use of heavy metals from anthropogenic activity. Two commercially important fish Prochilodus magdalenae and Pimelodus blochii, were cap- tured in four of the most important fishing municipalities in Tolima-Colombia, to determine the levels of cadmium, lead (Atomic absorption spectroscopy) and nickel (colorimetric) in the muscle, gill and liver. Pimelodus blochii is the one who bioac- cumulates these chemical pollutants in major quantity, with concentrations of Cad- mium from 0.009 ± 0.001 to 0.340 ± 0.402; lead from 0 to 8.737 ± 1.299 and Nickel from 2.26 ± 1.59 to 31.69 ± 10.26 mg/kg; the port of Flandes stands out as one of the areas of major ecological impact. There was correlation between cadmium concen- trations accumulated and the animal organ which acts as a metal reservoir, showing elevated levels for the liver tissue.